Analisa Perbandingan Throughput Komunikasi Data 4G Di Kota Mataram Menggunakan Wireshark - Djul Fikry Budiman; Sudi M. Al Sasongko (Depertment of Electrical Engineering University of Mataram, 2024)
The public's need to get high-speed internet services that can be accessed anywhere is a current need. One of the internet network services that is often accessed by the public is video streaming. The emergence of cellular providers with various advantages, each of which is a challenge in choosing a reliable provider. To find out which telecommunications provider/organizer is good for use in an area, especially in the city of Mataram, throughput values were measured using the Wireshark application. The main goal is to find out the throughput value which is a comparison of the download and upload sides. The morning measurement results using provider A had an average value of 484.76 kbps, in the afternoon it was 493.97 kbps and in the evening 401.65 kbps. Meanwhile, measurements using provider B have an average value of 1187.13 kbps in the morning, 1280.04 kbps in the afternoon and 844.46 kbps in the evening. From the calculation results obtained, it was concluded that provider B was better than provider A.